A lithium-carbon dioxide battery comprising a redox mediator and a hkust-1 modified separator

CN123017998APending Publication Date: 2026-10-30NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611173522.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]针对现有锂-二氧化碳电池存在的充放电过电位高、氧化还原介质易发生穿梭效应导致不可逆损耗、锂负极循环稳定性差的问题,本发明的目的是提供一种含氧化还原介质与HKUST-1修饰隔膜的锂-二氧化碳电池,以解决上述现有技术存在的问题

Benefits of technology

本发明采用HKUST-1改性隔膜,可有效抑制电解液中碘物种的扩散,显著降低氧化还原介质的不可逆损耗,与氧化还原介质形成协同作用,大幅提升了锂-二氧化碳电池的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017998A_ABST
    Figure CN123017998A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of metal-gas battery technology, and more specifically relates to a lithium-carbon dioxide battery containing a redox medium and an HKUST-1 modified separator. The lithium-carbon dioxide battery provided by this invention includes a positive electrode, a negative electrode, an electrolyte, and an HKUST-1 modified separator. 1-Ethyl-3-methylimidazolium iodide is added to the electrolyte as a redox medium, and its anion... ‑ I2 can accelerate the oxidation kinetics of Li2CO3, reduce the overpotential during battery charge and discharge, and improve the decomposition efficiency of the discharge product, lithium carbonate. The HKUST-1 modified separator is a single-sided modified structure with a HKUST-1 functional layer loaded on one side of the substrate, which can inhibit the diffusion of iodine species and reduce the loss of redox media. The lithium-carbon dioxide battery designed in this invention effectively solves the core problems of high overpotential during charge and discharge and poor cycle stability in lithium-carbon dioxide batteries, and improves the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal-gas battery technology, and more specifically relates to a lithium-carbon dioxide battery containing a redox medium and an HKUST-1 modified separator. Background Technology

[0002] Lithium-carbon dioxide batteries have the dual advantages of carbon dioxide resource utilization and ultra-high theoretical specific energy, with a theoretical specific energy as high as 1876 Wh / kg. They have broad application prospects in deep space exploration, emergency energy storage in extreme environments, and grid-scale energy storage, and are currently a research hotspot for next-generation energy storage battery systems.

[0003] However, the practical application of lithium-carbon dioxide batteries still faces a core bottleneck: lithium carbonate (Li2CO3) generated during battery discharge is a highly insulating material that is difficult to completely decompose during charging. It will continue to accumulate on the surface of the positive electrode, which will not only cover the reactive sites but also block the gas transport channels, ultimately leading to a sharp increase in battery voltage during charging, a significant decrease in charge and discharge efficiency, and a rapid shortening of cycle life.

[0004] Soluble redox media are currently an effective means to solve the problem of lithium carbonate decomposition. Among them, 1-ethyl-3-methyliodimidazolium iodide redox media can diffuse freely in the electrolyte, transforming the originally slow solid-solid interface decomposition reaction into a more efficient liquid-solid reaction, which significantly reduces the battery charging overpotential.

[0005] However, this type of iodine-based redox medium has inherent and unavoidable drawbacks in practical use: the shuttle effect of the redox medium and the resulting irreversible loss of iodine species. During charging, the oxidized iodine species generated at the positive electrode diffuse with the electrolyte, freely pass through the glass fiber separator, and reach the lithium negative electrode side, where they react directly with metallic lithium. On the one hand, this causes continuous and irreversible consumption of iodine species, and the catalytic effect of the redox medium will be completely lost in the later stages of the cycle; on the other hand, it will exacerbate the side reactions inside the battery, ultimately leading to rapid battery failure.

[0006] Therefore, how to specifically block the diffusion loss of oxidized iodine species without affecting the normal transport of lithium ions has become a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0007] To address the problems of high charge / discharge overpotential, irreversible losses due to shuttle effect in redox media, and poor cycle stability of lithium anode in existing lithium-carbon dioxide batteries, the present invention aims to provide a lithium-carbon dioxide battery containing a redox medium and an HKUST-1 modified separator to solve the aforementioned problems in the prior art.

[0008] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of the present invention is to provide an HKUST-1 modified diaphragm, comprising a substrate and an HKUST-1 functional layer loaded on one side of the substrate.

[0009] Furthermore, the substrate comprises glass fiber.

[0010] Furthermore, the loading amount of the HKUST-1 functional layer on the substrate is 2~3 mg / cm². 2 .

[0011] The second technical solution of the present invention provides a method for preparing the above-mentioned HKUST-1 modified separator, the steps of which include: HKUST-1 crystal powder was dispersed in a solvent to obtain an HKUST-1 dispersion; The HKUST-1 dispersion was loaded onto one side of a glass fiber membrane by vacuum filtration and dried to form an HKUST-1 functional layer, thus obtaining the HKUST-1 modified membrane.

[0012] Furthermore, the solvent is at least one of ethanol, methanol, isopropanol, N-methylpyrrolidone, or N,N-dimethylformamide.

[0013] Furthermore, the concentration of the HKUST-1 dispersion is 0.5~5 mg / mL.

[0014] In this invention, vacuum filtration employs a single-sided closed filtration device, allowing the dispersion to pass through only one side of the diaphragm.

[0015] The third technical solution of the present invention provides an application of the above-mentioned HKUST-1 modified separator in suppressing the redox medium shuttle effect in a metal-gas battery.

[0016] Fourth technical solution of the present invention: A lithium-carbon dioxide battery is provided, comprising the above-mentioned HKUST-1 modified separator and electrolyte; The electrolyte includes lithium salt, aprotic solvent, and redox medium; The redox medium is 1-ethyl-3-methyliodide imidazole.

[0017] Furthermore, the concentration of 1-ethyl-3-methyliodimazole in the electrolyte is 0.001~0.25 mol / L.

[0018] Furthermore, the lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

[0019] Furthermore, the concentration of the lithium salt in the electrolyte is 0.1~2 mol / L.

[0020] Furthermore, the aprotic solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, dimethyl sulfoxide, tetraethylene glycol dimethyl ether, and 1,3-dioxolane.

[0021] During battery assembly, the modified surface of the HKUST-1 modified separator (HKUST-1 functional layer) faces the positive electrode, while the unmodified exposed substrate faces the lithium metal negative electrode.

[0022] Furthermore, the preparation steps of the electrolyte include: dissolving lithium salt in an aprotic solvent and stirring until completely dissolved to obtain a basic electrolyte; adding 1-ethyl-3-methyliodide imidazole to the basic electrolyte and stirring at 20~25 °C for 20~24 h until completely mixed to obtain the electrolyte.

[0023] The present invention discloses the following technical effects: This invention uses HKUST-1 modified separator, which can effectively inhibit the diffusion of iodine species in electrolyte, significantly reduce irreversible loss of redox medium, form a synergistic effect with redox medium, and greatly improve the cycle stability of lithium-carbon dioxide battery.

[0024] This invention effectively reduces the charge / discharge overpotential of lithium-carbon dioxide batteries and improves the decomposition efficiency of the discharge product Li2CO3 by using 1-ethyl-3-methylimidazolium iodide redox medium.

[0025] The HKUST-1 modified separator provided by this invention can suppress the redox medium shuttle effect. When used in battery manufacturing, it does not require adjustment of the core structure of the positive and negative electrodes, and the manufacturing process is simple. The separator modified with HKUST-1 has an adjustable pore structure and abundant active sites, which can specifically block the diffusion loss of oxidized iodine species without affecting the normal transport of lithium ions. In synergy with the electrolyte in this invention, it can solve the problems of high charge and discharge overpotential, irreversible loss caused by the redox medium shuttle effect, and poor cycle stability of lithium negative electrode in existing lithium-carbon dioxide batteries.

[0026] The lithium-carbon dioxide battery provided by this invention includes a positive electrode, a negative electrode, an electrolyte, and an HKUST-1 modified separator. 1-Ethyl-3-methylimidazolium iodide is added to the electrolyte as a redox medium, and its anion has a positive effect on I3+. -I2 can accelerate the oxidation kinetics of Li2CO3, reduce the overpotential during battery charge and discharge, and improve the decomposition efficiency of the discharge product, lithium carbonate. The HKUST-1 modified separator is a single-sided modified structure with an HKUST-1 functional layer loaded on one side of the substrate, which can inhibit the diffusion of iodine species and reduce the loss of redox media. The lithium-carbon dioxide battery designed in this invention effectively solves the core problems of high overpotential during charge and discharge and poor cycle stability in lithium-carbon dioxide batteries, and improves the cycle life of the battery. Attached Figure Description

[0027] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is the molecular structural formula of 1-ethyl-3-methyliodimazole, the redox medium used in this invention.

[0028] Figure 2 Cyclic voltammetry (CV) curves of 1-ethyl-3-methylimidazolium iodide redox medium under CO2 and argon atmospheres, respectively.

[0029] Figure 3 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Example 1 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0030] Figure 4 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Comparative Example 1 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0031] Figure 5 The graph shows the cycle performance of the lithium-carbon dioxide battery in Comparative Example 2 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0032] Figure 6 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Comparative Example 3 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0033] Figure 7 The graphs show the first charge-discharge test results of lithium-carbon dioxide batteries of Examples 1, 4, 5 and 6 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0034] Figure 8 The charge-discharge curves of the lithium-carbon dioxide batteries of Example 1 and Comparative Example 2 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g for the 50th cycle are shown.

[0035] Figure 9 The image shows a scanning electron microscope (SEM) image of the HKUST-1 crystal powder prepared according to the present invention.

[0036] Figure 10 The images show a surface SEM comparison of the commercial glass fiber membrane and the HKUST-1 modified membrane in this invention, where a is the HKUST-1 modified membrane and b is the commercial glass fiber membrane.

[0037] Figure 11 X-ray diffraction (XRD) patterns of commercial glass fiber diaphragm (GF), HKUST-1 crystal powder (HKUST-1), and H-GF. Detailed Implementation

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0040] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0041] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0042] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0043] Unless otherwise specified, all raw materials and reagents involved in the specific embodiments of this invention are commercially available products.

[0044] The commercially available glass fiber diaphragm used in the specific embodiments of this invention was purchased from Waterman Corporation.

[0045] The HKUST-1 crystal powder used in the specific embodiments of this invention can be a commercially available product or a self-made product. A self-made method suitable for this invention is given below and used in the following examples and comparative examples. The steps include: 0.35 g Cu(NO3)2·3H2O and 0.2 g 1,3,5-benzenetricarboxylic acid were dissolved in a mixed solvent of N,N-dimethylformamide / ethanol / water with a volume ratio of 1:1:1 and a total volume of 60 mL. The mixture was transferred to a 100 mL high-pressure reactor lined with polytetrafluoroethylene and heated to 348 K and kept at that temperature for 24 h. After the reaction was completed, the blue crystals were collected by filtration, washed three times with water and acetone, and dried under vacuum to obtain HKUST-1 crystal powder.

[0046] In a specific embodiment of this invention, the carbon-based cathode is prepared by loading Ketjen black onto carbon paper. The mass ratio of Ketjen black to PVDF binder is 9:1. The current density of the battery is calculated based on the loaded mass of Ketjen black on the cathode. The preparation steps are as follows: S1. Weigh 90 mg of Ketjen black (KB) and 10 mg of polyvinylidene fluoride (PVDF), place them in a mortar and grind them thoroughly until they are mixed evenly.

[0047] S2. Transfer the ground mixed powder to a weighing bottle, add 10 mL of N-methyl-2-pyrrolidone (NMP), and stir at 25 ℃ and 500 rpm for 6 h to disperse evenly and obtain the positive electrode slurry.

[0048] S3. Cut the carbon paper into circular electrode sheets with a diameter of 12 mm, and add 25 μL of the above positive electrode slurry to each electrode sheet.

[0049] S4. The coated electrode is dried in a vacuum oven at 70 °C for 6 h to obtain a carbon-based cathode. The loading of Ketjen black on a single electrode is 0.20 mg. The current density of the battery test is calculated based on the loading mass of Ketjen black.

[0050] All reagents used in this invention are commercially available in battery-grade or analytical grade form; all operations involving water and oxygen sensitivity are performed in an argon atmosphere glove box with water and oxygen content both below 0.01 ppm; all electrochemical performance tests of the batteries are performed under pure CO2 atmosphere and at room temperature.

[0051] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of this invention refer to 20-30℃.

[0052] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0053] Figure 1 This is the molecular structural formula of 1-ethyl-3-methyliodimazole, the redox medium used in this invention.

[0054] Example 1 The preparation steps of a lithium-carbon dioxide battery include: Preparation of S1 and HKUST-1 modified diaphragms: S1.1 Disperse the above HKUST-1 crystal powder in anhydrous ethanol to prepare a dispersion with a concentration of 1 mg / mL.

[0055] S1.2. Based on the area of ​​the glass fiber diaphragm, at 2.5 mg / cm² 2 The amount of HKUST-1 required for loading was calculated. The dispersion was filtered under vacuum and uniformly loaded onto one side of a commercial glass fiber membrane (GF / D, Whatman). The membrane was dried at room temperature to obtain the HKUST-1 modified membrane, denoted as H-GF.

[0056] S2. Electrolyte preparation: S2.1 In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0057] S2.2. Place 1-ethyl-3-methylimidazolium iodide in a vacuum oven at 70 °C and dry for 24 h to complete the pretreatment.

[0058] S2.3 Add the dried 1-ethyl-3-methyliodide imidazole to the basic electrolyte at a concentration of 0.2 M, and stir at 25 °C for 24 h until completely mixed to obtain an electrolyte containing a redox medium.

[0059] S3, Battery Assembly: S3.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution and coat it onto the HKUST-1 functional layer of the HKUST-1 modified diaphragm by vacuum filtration. Place it in a vacuum oven at 60 ℃ and dry for 24 h to form a PVDF adhesive layer. Before transferring it to the glove box, perform degassing treatment. S3.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S3.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the exposed glass fiber substrate of the membrane faces the lithium metal negative electrode. S3.3. Add 50 μL of the electrolyte containing the redox medium prepared in step S2.3 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted; S3.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S3.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0060] Comparative Example 1 Compared to Example 1, the electrolyte of the lithium-carbon dioxide battery is the 1 M basic electrolyte prepared in step S2.1, and the separator is a commercial glass fiber separator. The steps include: The preparation steps of a lithium-carbon dioxide battery include: S1. Electrolyte preparation: In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0061] S2, Battery Assembly: S2.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution, apply it to one side of a commercial glass fiber membrane by vacuum filtration, and dry it in a vacuum oven at 60 °C for 24 h to form a PVDF adhesive layer. Before transferring it to a glove box, perform degassing treatment. S2.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S2.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the exposed glass fiber substrate of the membrane faces the lithium metal negative electrode. S2.3. Add 50 μL of the 1 M basic electrolyte prepared in step S1 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted. S2.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S2.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0062] Comparative Example 2 The difference from Example 1 is that the diaphragm is a commercially available glass fiber diaphragm, and the steps include: S1. Electrolyte preparation: S1.1 In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0063] S1.2. Place 1-ethyl-3-methylimidazolium iodide in a vacuum oven at 70 °C and dry for 24 h to complete the pretreatment.

[0064] S1.3 Add the dried 1-ethyl-3-methyliodide imidazole to the basic electrolyte at a concentration of 0.2 M, and stir at 25 °C for 24 h until completely mixed to obtain an electrolyte containing a redox medium.

[0065] S2, Battery Assembly: S2.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution, apply it to one side of a commercial glass fiber membrane by vacuum filtration, and dry it in a vacuum oven at 60 °C for 24 h to form a PVDF adhesive layer. Before transferring it to a glove box, perform degassing treatment. S2.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S2.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the exposed glass fiber substrate of the membrane faces the lithium metal negative electrode. S2.3. Add 50 μL of the electrolyte containing the redox medium prepared in step S1.3 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted. S2.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S2.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0066] Comparative Example 3 Compared to Example 1, the electrolyte for the lithium-carbon dioxide battery is the 1 M basic electrolyte prepared in step S2.1, which includes: The preparation steps of a lithium-carbon dioxide battery include: Preparation of S1 and HKUST-1 modified diaphragms: S1.1 Disperse the above HKUST-1 crystal powder in anhydrous ethanol to prepare a dispersion with a concentration of 1 mg / mL.

[0067] S1.2. Based on the area of ​​the glass fiber diaphragm, at 2.5 mg / cm² 2 The required amount of HKUST-1 was calculated based on the loading amount. The dispersion was then filtered under vacuum and uniformly loaded onto one side of a commercial glass fiber membrane (GF / D, Whatman). The membrane was dried at room temperature to obtain the HKUST-1 modified membrane.

[0068] S2. Electrolyte preparation: In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0069] S3, Battery Assembly: S3.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution and coat it onto the HKUST-1 functional layer of the HKUST-1 modified diaphragm by vacuum filtration. Place it in a vacuum oven at 60 ℃ and dry for 24 h to form a PVDF adhesive layer. Before transferring it to the glove box, perform degassing treatment. S3.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S3.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the exposed glass fiber substrate of the membrane faces the lithium metal negative electrode. S3.3. Add 50 μL of the electrolyte containing redox medium prepared in step S2 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted. S3.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S3.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0070] Comparative Example 4 Compared to Example 1, the difference lies in that the HKUST-1 modified separator is placed closer to the lithium anode side, and the steps include: The preparation steps of a lithium-carbon dioxide battery include: Preparation of S1 and HKUST-1 modified diaphragms: S1.1 Disperse the above HKUST-1 crystal powder in anhydrous ethanol to prepare a dispersion with a concentration of 1 mg / mL.

[0071] S1.2. Based on the area of ​​the glass fiber diaphragm, at 2.5 mg / cm² 2The amount of HKUST-1 required for loading was calculated. The dispersion was filtered under vacuum and uniformly loaded onto one side of a commercial glass fiber membrane (GF / D, Whatman). The membrane was dried at room temperature to obtain the HKUST-1 modified membrane, denoted as H-GF.

[0072] S2. Electrolyte preparation: S2.1 In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0073] S2.2. Place 1-ethyl-3-methylimidazolium iodide in a vacuum oven at 70 °C and dry for 24 h to complete the pretreatment.

[0074] S2.3 Add the dried 1-ethyl-3-methyliodide imidazole to the basic electrolyte at a concentration of 0.2 M, and stir at 25 °C for 24 h until completely mixed to obtain an electrolyte containing a redox medium.

[0075] S3, Battery Assembly: S3.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution and coat it onto the HKUST-1 functional layer of the HKUST-1 modified diaphragm by vacuum filtration. Place it in a vacuum oven at 60 ℃ and dry for 24 h to form a PVDF adhesive layer. Before transferring it to the glove box, perform degassing treatment. S3.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S3.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the modified surface of the membrane faces the lithium metal negative electrode. S3.3. Add 50 μL of the electrolyte containing the redox medium prepared in step S2.3 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted; S3.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S3.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0076] Comparative Example 5 The difference compared to Example 1 is that the HKUST-1 modified diaphragm used has a loading of 10 mg / cm³. 2 The steps include: The preparation steps of a lithium-carbon dioxide battery include: Preparation of S1 and HKUST-1 modified diaphragms: S1.1 Disperse the above HKUST-1 crystal powder in anhydrous ethanol to prepare a dispersion with a concentration of 1 mg / mL.

[0077] S1.2. Based on the area of ​​the glass fiber diaphragm, at 10 mg / cm² 2 The amount of HKUST-1 required for loading was calculated. The dispersion was filtered under vacuum and uniformly loaded onto one side of a commercial glass fiber membrane (GF / D, Whatman). The membrane was dried at room temperature to obtain the HKUST-1 modified membrane, denoted as H-GF.

[0078] S2. Electrolyte preparation: S2.1 In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0079] S2.2. Place 1-ethyl-3-methylimidazolium iodide in a vacuum oven at 70 °C and dry for 24 h to complete the pretreatment.

[0080] S2.3 Add the dried 1-ethyl-3-methyliodide imidazole to the basic electrolyte at a concentration of 0.2 M, and stir at 25 °C for 24 h until completely mixed to obtain an electrolyte containing a redox medium.

[0081] S3, Battery Assembly: S3.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution and coat it onto the HKUST-1 functional layer of the HKUST-1 modified diaphragm by vacuum filtration. Place it in a vacuum oven at 60 ℃ and dry for 24 h to form a PVDF adhesive layer. Before transferring it to the glove box, perform degassing treatment. S3.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassed membrane from step S3.1 into the negative electrode shell of the CR2032 button battery in sequence; wherein the exposed glass fiber substrate of the membrane faces the lithium metal negative electrode. S3.3. Add 50 μL of the electrolyte containing the redox medium prepared in step S2.3 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted; S3.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S3.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0082] Comparative Example 6 The difference compared to Example 1 is that the HKUST-1 modified diaphragm used is bifacially loaded, with a loading of 2.5 mg / cm² on both sides. 2 The steps include: The preparation steps of a lithium-carbon dioxide battery include: Preparation of S1 and HKUST-1 modified diaphragms: S1.1 Disperse the above HKUST-1 crystal powder in anhydrous ethanol to prepare a dispersion with a concentration of 1 mg / mL.

[0083] S1.2. Based on the area of ​​the glass fiber diaphragm, at 2.5 mg / cm² 2 The amount of HKUST-1 required for loading was calculated. The dispersion was filtered under vacuum and uniformly loaded onto both sides of a commercial glass fiber membrane (GF / D, Whatman). The membrane was dried at room temperature to obtain the HKUST-1 modified membrane, denoted as H-GF.

[0084] S2. Electrolyte preparation: S2.1 In an argon glove box with water and oxygen content below 0.01 ppm, lithium bis(trifluoromethanesulfonylimide) (LiTFSI) was dissolved in tetraethylene glycol dimethyl ether (TEGDME) and stirred at 300 rpm until completely dissolved to prepare a 1 M basic electrolyte.

[0085] S2.2. Place 1-ethyl-3-methylimidazolium iodide in a vacuum oven at 70 °C and dry for 24 h to complete the pretreatment.

[0086] S2.3 Add the dried 1-ethyl-3-methyliodide imidazole to the basic electrolyte at a concentration of 0.2 M, and stir at 25 °C for 24 h until completely mixed to obtain an electrolyte containing a redox medium.

[0087] S3, Battery Assembly: S3.1 Dissolve PVDF in NMP to prepare a PVDF colloidal solution with a concentration of 0.05 mg / mL. Take 10 mL of the above PVDF colloidal solution and coat it onto the HKUST-1 functional layer of the HKUST-1 modified diaphragm by vacuum filtration. Place it in a vacuum oven at 60 ℃ and dry for 24 h to form a PVDF adhesive layer. Before transferring it to the glove box, perform degassing treatment. S3.2 In an argon glove box, place the spring sheet, gasket, lithium metal sheet negative electrode, and the degassing membrane from step S3.1 into the negative electrode shell of the CR2032 button battery in sequence. S3.3. Add 50 μL of the electrolyte containing the redox medium prepared in step S2.3 to the surface of the diaphragm to ensure that the diaphragm and the electrode are fully wetted; S3.4 Place the carbon-based positive electrode prepared above on the other side of the separator so that the PVDF adhesive layer adheres to the carbon-based positive electrode; S3.5 After covering the positive electrode shell and sealing it, place it in a pure CO2 atmosphere and let it stand for 5 hours to obtain a lithium-carbon dioxide battery.

[0088] Electrochemical performance testing: Constant current charge-discharge tests and long-cycle stability tests of all batteries were conducted using the Land battery testing system, with a test voltage range of 2.0~4.5 V; Cyclic voltammetry (CV) tests were conducted using the Shanghai Chenhua CHI760E electrochemical workstation, with a scan voltage range of 2.0~4.5 V and a scan rate of 0.1 mV / s, under CO2 and argon atmospheres respectively.

[0089] Figure 2 Cyclic voltammetry (CV) curves of 1-ethyl-3-methylimidazolium iodide redox medium under CO2 and argon atmospheres, respectively.

[0090] Figure 3 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Example 1 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0091] Figure 4 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Comparative Example 1 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0092] Figure 5 The graph shows the cycle performance of the lithium-carbon dioxide battery in Comparative Example 2 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0093] Figure 6 The graph shows the cycle performance test results of the lithium-carbon dioxide battery in Comparative Example 3 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0094] Figure 7 The graphs show the first charge-discharge test results of lithium-carbon dioxide batteries of Examples 1, 4, 5 and 6 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g.

[0095] Figure 8 The charge-discharge curves of the lithium-carbon dioxide batteries of Example 1 and Comparative Example 2 at a current density of 500 mA / g and a cutoff capacity of 1000 mAh / g for the 50th cycle are shown.

[0096] Depend on Figure 2-8 It can be seen that: The 1-ethyl-3-methylimidazolium iodide redox medium used in this invention possesses excellent liquid-phase catalytic activity, transforming the originally slow Li₂CO₃ solid-solid interface decomposition reaction into a highly efficient liquid-solid reaction. Cyclic voltammetry tests show that the oxidation current of this medium is significantly increased under a CO₂ atmosphere, confirming its effective catalytic decomposition of discharge products and a substantial reduction in battery overpotential.

[0097] In Comparative Example 4 (modified side facing negative electrode), the overpotential increased significantly due to the Cu in HKUST-1. 2+ The site directly contacts the lithium anode, causing a reduction side reaction that damages the framework structure and increases the interfacial impedance.

[0098] Comparative Example 5 (10 mg / cm) 2 Under high load, the overpotential increases significantly because the excessively thick MOF layer greatly increases the resistance to lithium-ion transport, resulting in an increase in battery impedance.

[0099] In Comparative Example 6 (double-sided load), the overpotential during the first charge-discharge cycle is the highest, due to the dual adverse effects of negative electrode side reaction and increased double-sided mass transfer impedance.

[0100] In summary, this invention selects 2.5 mg / cm³. 2 The scheme of single-sided loading with the modified surface facing the positive electrode represents the optimal balance between the iodine species shuttle inhibition effect and the lithium-ion transport efficiency.

[0101] This invention applies HKUST-1 modified separator and electrolyte containing redox media as a synergistic system to lithium-carbon dioxide batteries, resulting in significant performance improvements under current density of 500 mA / g and capacity limitation of 1000 mAh / g. The blank control group (Comparative Example 1) and batteries using only the HKUST-1 modified separator (Comparative Example 3) could only cycle stably for about 30 hours before the charging overpotential spiked sharply to over 4.5V. The battery with only the added redox media (Comparative Example 2) showed improved cycle stability, cycling stably for about 270 hours, but the overpotential continued to rise due to media shuttle loss, and the redox media activity weakened after the 50th cycle. In contrast, the synergistic system battery of this invention (Example 1), through the dual effects of catalytic decomposition and shuttle inhibition, maintained redox media activity in the charge-discharge curve after 50 stable cycles, achieving stable cycling for over 600 hours. The charge-discharge plateau remained stable during cycling, solving the core problems of high charge-discharge overpotential and short cycle life in lithium-carbon dioxide batteries.

[0102] Morphology and structure characterization: The surface morphology of HKUST-1 material and the diaphragm before and after modification was characterized by scanning electron microscopy (SEM); the crystal phase structure of HKUST-1 material was characterized by X-ray diffraction (XRD), with a test range of 5° to 50°.

[0103] Figure 9 The image shows a scanning electron microscope (SEM) image of the HKUST-1 crystal powder prepared according to the present invention.

[0104] Figure 10 The images show a surface SEM comparison of the commercial glass fiber membrane and the HKUST-1 modified membrane in this invention, where a is the HKUST-1 modified membrane and b is the commercial glass fiber membrane.

[0105] Figure 11 X-ray diffraction (XRD) patterns of commercial glass fiber diaphragm (GF), HKUST-1 crystal powder (HKUST-1), and H-GF.

[0106] Depend on Figures 9-11 As can be seen, this invention successfully prepared a highly crystalline pure-phase HKUST-1 material via a solvothermal method. This material exhibits a uniform octahedral crystal structure without significant agglomeration. When loaded onto a glass fiber membrane, it forms a dense and continuous functional layer. XRD characterization confirmed that the loading process did not damage the material's crystal structure, providing a structural basis for inhibiting the diffusion of iodine species across the membrane.

[0107] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0108] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An HKUST-1 modified diaphragm, characterized in that, It includes a substrate and an HKUST-1 functional layer loaded on one side of the substrate.

2. The HKUST-1 modified diaphragm as described in claim 1, characterized in that, The substrate includes glass fiber; And / or, the loading amount of the HKUST-1 functional layer on the substrate is 2~3 mg / cm³. 2 .

3. A method for preparing the HKUST-1 modified diaphragm according to claim 1 or 2, characterized in that the step include: HKUST-1 crystal powder was dispersed in a solvent to obtain an HKUST-1 dispersion; The HKUST-1 dispersion was loaded onto one side of a glass fiber membrane by vacuum filtration and dried to form an HKUST-1 functional layer, thus obtaining the HKUST-1 modified membrane.

4. The preparation method according to claim 3, characterized in that, The solvent is at least one of ethanol, methanol, isopropanol, N-methylpyrrolidone, or N,N-dimethylformamide.

5. The preparation method according to claim 3, characterized in that, The concentration of the HKUST-1 dispersion is 0.5~5 mg / mL.

6. The application of the HKUST-1 modified separator as described in claim 1 or 2 in suppressing the redox shuttle effect in a metal-gas battery.

7. A lithium-carbon dioxide battery, characterized in that, Includes the HKUST-1 modified diaphragm and electrolyte as described in claim 1 or 2; The electrolyte includes lithium salt, aprotic solvent, and redox medium; The redox medium is 1-ethyl-3-methyliodide imidazole.

8. The lithium-carbon dioxide battery as described in claim 7, characterized in that, The concentration of 1-ethyl-3-methyliodimazole in the electrolyte is 0.001~0.25 mol / L.

9. The lithium-carbon dioxide battery as described in claim 7, characterized in that, The lithium salt includes at least one of lithium bis(trifluoromethanesulfonylimide), lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate, and has a concentration of 0.1~2 mol / L in the electrolyte.

10. The lithium-carbon dioxide battery as described in claim 7, characterized in that, The aprotic solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, dimethyl sulfoxide, tetraethylene glycol dimethyl ether, and 1,3-dioxolane.